2015
DOI: 10.1097/ajp.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Pressure Pain Hypersensitivity in Patients With Multiple Sclerosis With and Without Pain as Sign of Central Sensitization

Abstract: Our study found widespread pressure pain hyperalgesia in individuals with MS as compared with pain-free controls. No differences existed between MS patients with pain and those without pain in the presence of widespread pressure sensitivity. Current results suggest that MS is associated with sensory hyperexcitability of the central nervous system or dysfunction in endogenous pain modulatory systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…This theory was previously supported by our group, who used an algometer to measure the thermal and discomfort thresholds and demonstrated significantly lower values in MS patients than healthy controls, irrespectively of the presence of pain [5]. These data have also been recently confirmed by Fernández et al, who demonstrated widespread pressure pain hypersensitivity even in MS patients without pain [6]. The broad categories of MS-related pain are the central neuropathic pain, which include the most common dysesthetic extremity pain, musculoskeletal pain, including back pain, painful tonic spasms and headache; pain in MS can be paroxystic, acute or chronic [7].…”
Section: Introductionsupporting
confidence: 72%
“…This theory was previously supported by our group, who used an algometer to measure the thermal and discomfort thresholds and demonstrated significantly lower values in MS patients than healthy controls, irrespectively of the presence of pain [5]. These data have also been recently confirmed by Fernández et al, who demonstrated widespread pressure pain hypersensitivity even in MS patients without pain [6]. The broad categories of MS-related pain are the central neuropathic pain, which include the most common dysesthetic extremity pain, musculoskeletal pain, including back pain, painful tonic spasms and headache; pain in MS can be paroxystic, acute or chronic [7].…”
Section: Introductionsupporting
confidence: 72%
“…These results show that overactive endogenous pain facilitation is characteristic of pain symptoms in CFS, but not in MS. This is consistent The presence of widespread hyperalgesia in people with CFS is not a novel finding (10,26,27), but this aspect of pain has only recently been reported in people with MS (12). The exact mechanisms underlying pain and widespread hyperalgesia in MS have not been elucidated.…”
Section: Discussionsupporting
confidence: 62%
“…Similarities and differences in pain experienced by patients with CFS or MS have yet to be explored as a potential means of gaining insight into the causal background of pain symptoms. In particular, central sensitization, i.e., increased excitability of the central nervous system, has been demonstrated in CFS (10,11), and has been posited to play a role in MS, albeit on the basis of one study which reported widespread hyperalgesia in patients with MS (12). Central sensitization is characterized by impaired endogenous pain inhibition (13) and overactive endogenous pain facilitation (14).…”
mentioning
confidence: 99%
“…Central Sensitization has been most often identified with fibromyalgia, and associated chronic widespread pain and sensitivity, with no observable pathology or nociceptive etiology. However, CS has also been identified in subsets of patients with clear evidence of tissue trauma, pathology, and/or nociceptive components, including multiple sclerosis (Fernández‐de‐las‐Peñas et al., ), osteoarthritis (Akinci et al., ; Lluch, Torres, Nijs, & Van Oosterwijck, ), rheumatoid arthritis (Meeus et al., ), and post‐surgical breast cancer (Fernández‐Lao et al., ). Interestingly CS has also been tied to various other conditions in which pain is not a primary symptom, including post‐traumatic stress disorder, multiple chemical sensitivity, restless leg syndrome (Yunus, , ) over‐active bladder (Reynolds, Dmochowski, Wein, & Bruehl, ), and chronic hives (Torresani, Bellafiore, & De Panfilis, ), suggesting that CS may not only be associated with pain hypersensitivity but can also involve hypersensitivity to other stimuli, including lights, sounds, fragrances, skin irritants, bodily sensations, and stress‐evoking life events (Nijs, Goubert, & Ickmans, ; Yunus, , ).…”
Section: Central Sensitizationmentioning
confidence: 99%